Estudo da prevalência dos genótipos e mutações de resistência associadas aos antivirais em pacientes com hepatite B crônica atendidos nos serviços de referência do Estado do Ceará - Cruz, José Napoleão Monte da (2015)
Infection with hepatitis B virus (VHB) is a serious public health problem. An estimated 450 million chronic carriers worldwide, where at least 600,000 people die annually from diseases related to hepatitis B. Viral load, HBe seroconversion-antiHBe, and specific genotype and viral mutations are acquired factors influence the progression of the disease. The aim of this study was to investigate the prevalence of VHB resistance mutations associated with antiviral and evaluate the genotype distribution in a sample of 142 patients with chronic hepatitis B, treated in the State of Ceará referral hospitals. Patients were considered reactive serum HBsAg for at least six months. Serological tests were performed by electrochemiluminescence (EQL), ABBOTT laboratory for HBsAg, HBeAg and anti-HBe. The results of the serological screening showed that all samples: 142 (100%) were reactive serum HBsAg (IgG), 87 (61.0%) were negative to serum and serum HBeAg to anti-HBe reagent, 55 (39, 0%) are seroreactive for HBe and serum non-reactive for anti-HBe. The quantitation of viremia (viral load) was performed by real time PCR (QPCR) in LACEN-EC. The viral load varied between the limits (2067 IU / ml to 3.41 billion IU / ml), with a median of 70 403 IU / ml. Eighty-eight (62%) of all samples were submitted to analysis of mutations associated with treatment and genotyping the Hepatitis laboratory of the FIOCRUZ-RJ, screened for sequencing as quality criteria and routine laboratory biosafety this. The identification of genotypes in the population studied showed the following distribution: F: 47 (53.4%) of A: 34 (38.6%), the D: 4 (4.6%), E: 2 ( 2.3%) and G 1 (1.1%). And the following mutations were detected: L180M (n = 10 / 9.9%), M204V (n = 8 / 7.9%), M204I (n = 4/4%), G173L (n = 1/1%) , T169L (n = 1/1%), T184I (n = 1/1%), L80V (n = 1/1%) while 74.3% showed no change. In the study it was observed that the F genotype (53.4%) was the most prevalent in the research population of Indian origin, followed by genotype (38.6%) due to migration of African slaves. And, the higher frequency of the detected mutations are associated with nucleoside inhibitors and nucleotides, especially lamivudine.